Horngren's Cost Accounting: A Managerial Emphasis - Datar, Srikant M. (Pearson Education (US), 2025)
For undergraduate and MBA courses in cost accounting or management accounting. The text that defined the cost accounting market Horngren’s Cost Accounting expertly demonstrates how cost accounting can help managers make good decisions. Guided by the theme of “different costs for different purposes,” this acclaimed text positions cost accounting as a tool for business strategy, rather than just a set of procedures. Its flexible modules let you adapt the material to your course needs. The 18th Edition illustrates cost accounting practices through the lens of cutting-edge topics such as generative AI and repercussions of the coronavirus pandemic. Dozens of new real-world examples show how cost accounting can be used to support sustainability, innovation, and shifts in the US and global economies.